Genomic Analysis of KPC-2-Producing Klebsiella pneumoniae ST11 Isolates at the Respiratory Department of a Tertiary Care Hospital in Beijing, China - Guo, Ling; Wang, Lifeng; Zhao, Qiang; Ye, Liyan; Ye, Kun; Ma, Yanning; Shen, Dingxia; Yang, Jiyong (Frontiers in Microbiology, 2022)
Background. Carbapenem-resistant Klebsiella pneumoniae (CRKP) is an important pathogen causing hospital-associated outbreaks worldwide. The spread of KPC-2 producing CRKP is primarily associated with sequence type (ST) 11. Methods. A total of 152 KPC-2 producing K. pneumoniae ST11 isolates were collected from the respiratory department of a tertiary care hospital in Beijing, China between 2009 and 2018. The genome sequencing of these isolates was performed on a HiSeq X Ten sequencer.MLST, capsular type and plasmid MLST, capsular type and plasmid replicon types and resistance genes were identified. Fifteen isolates were selected for the subsequent single-molecule real-time (SMRT) sequencing on a PacBio RS II. Alignment of the complete sequences of the plasmids carrying blaKPC-2 and/or virulence genes was performed by using BRIG and Easyfig. Results. From 2012 to 2018, the detection rate of the blaKPC-2-carrying CRKP rised rapidly from 3.3% to 28.1%. KPC-2 producing K. pneumoniae ST11 isolates were dominant in CRKP, which emerged in 2012 and caused several outbreaks. Most isolates exhibited multi-drug resistant to common used antibiotics, while all isolates remained susceptible to tigecycline and polymyxin B. The SNP analysis showed that all these 152 KPC-2 producing K. pneumoniae ST11 isolates could be divided into three genetically distinct clades (A, B, C) and eleven subcaldes(A1-A9, B1-B2). The majority belonged to clade A with KL47 serotype (n=117, 77.0%), while KL64 and KL16 were identified in clade B and C, respectively. The blaKPC-2-carrying plasmids exhibited diverse types, including IncFII(pHN7A8)/IncR(6/15), IncFII(pHN7A8)/IncpA1763-KPC (5/15), IncFII (pHN7A8) (1/15), IncR (1/15), and IncpA1763-KPC (1/15). The genetic environment of blaKPC-2 showed nine IS26-based composite transposons which had a basic core structure ISKpn27-blaKPC-2-ΔISKpn6 structure forms. About 27.6% (42/152) isolates co-carried 2 to 4 virulence marker genes (including peg344, iucA, iroB, rmpA and rmpA2) for hvKp strains. At least three isolates were identified to harbor virulence-gene-carrying plasmids. Conclusions. KPC-2 producing K. pneumoniae ST11 were highly heterogeneous in our hospital. Transmission of these strians was mainly mediated by twelve high-risk clones. The blaKPC-2-carrying plasmids and genetic environment of blaKPC-2 genes exhibited active evolution in K. pneumoniae ST11. More attention should be paid to the tendency of KPC-2-ST11 to acquire hypervirulent plasmids.